ICHTHYOFAUNAL DIVERSITY AND WATER QUALITY OF PARAPPAR RESERVOIR IN KOLLAM DISTRICT, KERALA, INDIA - SHANIMOL, B.; SAHIB, S. SYNUDEEN (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2020)
Parappar reservoir is the second largest irrigation project in Kerala. Water from the reservoir is also used for power generation and drinking purpose. The dam water is being distributed to three districts of Kerala such as Kollam, Pathanamthitta and Alappuzha. The surface water bodies, which are the most important source of water for human activities are unfortunately under severe environmental stress and are being threatened as a consequence of developmental activities. Reservoir fish production is gradually becoming a significant contributor to total inland production and often provides a relatively affordable source of fresh and good quality animal protein source to many rural communities. The present study is an attempt to assess the biodiversity of fish fauna in the Parappar reservoir with reference to physico-chemical parameters of water from the reservoir. Water samples and fish were collected monthly for a period of one year from October 2017 to September 2018. Water quality parameters such as water temperature, pH, dissolved oxygen, biological oxygen demand, carbon dioxide and nitrate were selected for the present study. The result showed variations in the monthly mean values of all the water quality parameters tested. All the physico-chemical parameters tested were within the permissible limit as per the WHO standard (1993) and it was found suitable for fish production. The present study revealed the occurrence of 18 fish species belonging to 4 orders and 6 families. Shell fishe are totally absent during the entire study period. Cyprinidae dominated with eleven species and it is followed by Cichlidae, Bagridae, Channidae, Claridae and Heteropneustridae.